2013
DOI: 10.1007/s00128-013-1150-0
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution and Potential Ecological Risks in Rivers: A Case Study from Southern Italy

Abstract: We monitored heavy metal (As, Cd, Hg, and Pb) concentrations in surface water, sediments, and oligochaetes in four major rivers in Calabria (southern Italy) over the course of 1 year. As, Cd, and Pb showed accumulation factors of 10(3)-10(5) for water to sediment and 1-10 for sediment to oligochaetes. Hg showed a water to sediment accumulation factor of 10-100. Finally, Hg concentrations exceeded the Italian quality standard for freshwater in all of the rivers, and As concentrations in sediments exceeded the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…In general, the concentrations of dissolved Hg found in this study are comparable to or within the range reported for small streams in Europe (\0.001-1.08 lg L -1 ) (Protano et al 2014), Indonesia (0.08-0.22 lg L -1 ) (Yasuda et al 2011) and China (\0.01-0.69 lg L -1 ) (Lin et al 2012). The Ag levels found in this study were below or close to the mean dissolved Ag level reported in major unpolluted world rivers (0.3 lg L -1 ) (Martín and Meybeck 1979), which indicates that the influence of the spill on the dissolved Ag was not significant.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In general, the concentrations of dissolved Hg found in this study are comparable to or within the range reported for small streams in Europe (\0.001-1.08 lg L -1 ) (Protano et al 2014), Indonesia (0.08-0.22 lg L -1 ) (Yasuda et al 2011) and China (\0.01-0.69 lg L -1 ) (Lin et al 2012). The Ag levels found in this study were below or close to the mean dissolved Ag level reported in major unpolluted world rivers (0.3 lg L -1 ) (Martín and Meybeck 1979), which indicates that the influence of the spill on the dissolved Ag was not significant.…”
Section: Resultssupporting
confidence: 67%
“…It is generally assumed that differences between metal concentrations in the water and sediment samples are associated with long-term exposure in sediments, whereas metal concentrations in water indicate recent contamination (Protano et al 2014). From this scenario it is possible to argue for this case that a few days after the spill the dissolved metals were most enriched with those metals liberated from the tailings.…”
Section: Resultsmentioning
confidence: 99%
“…Among the contaminants, heavy metals should be highlighted due to the consequences of their bioaccumulation in aquatic ecosystems (Nadmitov et al 2014, Marques et al 2009, Sloman 2007. Significant quantities of these metals are discharged into rivers, where they can be strongly accumulated and biomagnified in water, sediment, and the aquatic food chain, resulting in both sub-lethal effects or death in local fish populations (Megeer et al 2000, Protano et al 2014, Xie et al 2014, Xu et al 2004. FÁBIO …”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals concentrations are also very important to evaluations of water quality. Contamination of groundwater by heavy metals has been found in agricultural areas (Wongsasuluk et al 2014), mining areas (Concas et al 2006;Kumari et al 2014), gulfs (Upadhyaya et al 2014), and river basins (Gupta et al 2009;Protano et al 2014;Sheykhi and Moore 2013;Singh et al 2014). REEs co-exist with elemental metals in minerals in mining area.…”
mentioning
confidence: 99%